Intervensi Mastery Experience dalam Eskalasi Kompetensi Diagnostik dan Overhaul Transmisi Otomatis di Sekolah Kejuruan - Suhartanta; Fajrin Sidiq Muzaffarul Zaman; Nirmala Adhi Yoga Pambayun (JURPIKAT, 2026)
The primary issue addressed in this community service program is the underutilization of automatic transmission practice facilities in vocational schools due to teachers' lack of confidence in modern technology. This program aims to support automotive instructors at SMK Muhammadiyah 1 Bambanglipuro in becoming more empowered to keep pace with industry dynamics. Using a 32-hour mastery experience approach, 10 participants delved into CVT and DCT technologies, including hands-on overhaul practices. Paired t-test analysis confirmed the program's success, showing an average score increase of 1.45 points. The most significant impact was seen in the teachers' self-efficacy index, which climbed from a baseline of 2.27 (low category) to 3.72 (high category), with peak achievement in preventive maintenance procedures (4.00). This intervention effectively overcomes the psychological barriers of educators, making them more confident in guiding their students. This success proves that strengthening teacher competency is the key to ensuring vocational education remains adaptive to industrial technology disruptions.